PESAN-PESAN MORAL DALAM FILM WONDER KARYA STEPHEN CHBOSKY - Sompotan, Winston Samuel Glenn Hizkia; Tulung, Golda Juliet; Marentek, Andriyani (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â The title of this research is â€œMoral Values in the Movie Wonder by Stephen Chboskyâ€ and it is intended as a requirement to accomplish a degree at the Faculty of Humanities Sam Ratulangi University. The aims of this study are to analyze the moral values in the movie Wonder through the portrayal of the main character named August Pullman and to identify the conflicts that the character deals with. Theories from a few experts are being applied in this study, such as theory from Pojman (2000) to unfold the morality in general, theory from Bohlin (2005) to unfold the morality in literature and conflict in characters, theory from Morrell (2009) to unfold the conflict and types of conflict in literature and theory from Roberts and Jacobs (1986) to unfold the function of conflict in literature. The results show that the main character, August Pullman, deals with several conflicts in his life such as conflict against syndrome, against low self-esteem, against bullying, and conflict to have a best friend; and the moral values out of all those conflicts that the main character deals with is that we need to be kind, do not lose faith in friendship, good personality is all that matters, true beauty comes from within, tears are the contemplation of self-motivation, things people deal make them who they are, and bullying could be a way to success.Keywords: Moral Values, Conflicts, August Pullman, The Movie Wonder.